Improving the technology of working with gifted students (Journal of Pedagogical Inventions and Practices, 2022)
In this article, several views on the importance of the personal activity of a gifted child, as well as the psychological mechanisms of self-development of a person underlying the formation and implementation of individual talent, have been put forward